How Salesperson Tactics and Online Convenience Shape Purchase Decisions: The Mediating Role of Trust - Haidar Achmad; I Gusti Ayu Ketut Giantari (International research journal of management, IT and social sciences, 2026)
Consumer preferences in furniture shopping have now shifted significantly towards online platforms, even though furniture is a complex item and requires careful consideration. This study aims to analyze the role of trust in mediating the influence of salesperson tactics and online convenience on purchase decisions among online consumers of Mahaghony Terrazzo in Bali Province. Salesperson tactics include persuasive approaches, information exchange, ingratiation, and promises, while online convenience encompasses ease of access, transactions, evaluation, and search. This study uses a quantitative approach; a survey of 160 Mahaghony Terrazzo consumers was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that trust is proven to mediate the relationship between salesperson tactics and online convenience on purchase decisions. The results of this study are expected to provide theoretical contributions to the development of marketing literature, particularly regarding the mediation mechanism of trust in the context of salesperson tactics and online convenience. This research contributes to the understanding of consumer behavior in the online furniture market and provides strategic implications for digital optimization and customer experience enhancement.